Comparative Antibacterial Activity of Citrus hystrix DC. Leaf Essential Oil Against ESBL Klebsiella pneumoniae and Multidrug-Resistant Serratia marcescens - Leka Lutpiatina; Norsyifa Norsyifa; Mahira Ainiyah Putri; Ratih Dewi Dwiyanti; Aima Insana (Tropical Health and Medical Research, 2026)
The increasing antimicrobial resistance has driven the development of natural antibacterial sources, one of which is essential oils. This study aimed to analyse the antibacterial activity of lime leaf essential oil (Citrus hystrix DC.) against Extended Spectrum ?-Lactamase (ESBL)-producing Klebsiella pneumoniae and multidrug-resistant Serratia marcescens. The study used a true experimental design with a posttest-only control group design. The essential oils were tested at concentrations of 50%, 60%, 70%, 80%, 90%, and 100% using the well diffusion method with four replications. Ciprofloxacin served as a positive control and dimethyl sulfoxide as a negative control. Data were analysed using the Shapiro–Wilk test, Levene's test, one-way ANOVA, or Welch ANOVA, followed by post hoc tests according to data characteristics at a significance level of p<0.05. The results showed that lime leaf essential oil had antibacterial activity against both bacteria at all concentrations tested. For Klebsiella pneumoniae ESBL, the inhibition zone diameter increased from 6.83 mm at 50% concentration to 9.30 mm at 90% concentration, then decreased to 8.08 mm at 100%. For multidrug-resistant Serratia marcescens, the inhibition zone diameter increased from 7.80 mm to 14.00 mm at 90% concentration, then decreased to 11.20 mm at 100%. Statistical analysis showed a significant difference between the concentrations for both bacteria (p<0.001). In general, Serratia marcescens showed higher sensitivity than Klebsiella pneumoniae ESBL. Although its inhibitory power was still lower than ciprofloxacin, lime leaf essential oil has the potential to be developed as a natural antibacterial source against resistant Gram-negative bacteria.